2008
DOI: 10.1890/080054
|View full text |Cite
|
Sign up to set email alerts
|

Potential habitat distribution for the freshwater diatom Didymosphenia geminata in the continental US

Abstract: The diatom Didymosphenia geminata is a single‐celled alga found in lakes, streams, and rivers. Nuisance blooms of D geminata affect the diversity, abundance, and productivity of other aquatic organisms. Because D geminata can be transported by humans on waders and other gear, accurate spatial prediction of habitat suitability is urgently needed for early detection and rapid response, as well as for evaluation of monitoring and control programs. We compared four modeling methods to predict D geminata's habitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 24 publications
0
116
1
2
Order By: Relevance
“…Maxent is a general-purpose machine learning method, which uses a maximum-entropy approach. Its application in species distribution modelling is fairly recent and gives superior results compared to other methods (Elith et al, 2006;Kumar et al, 2009;Phillips et al, 2006Phillips et al, , 2004Poulos et al, 2012). The prediction of the model indicates the areas within the study region that satisfy the requirements of the species' ecological niche.…”
Section: Vdc/distribution Modelling For Pterocarpus Angolensis -Appromentioning
confidence: 99%
“…Maxent is a general-purpose machine learning method, which uses a maximum-entropy approach. Its application in species distribution modelling is fairly recent and gives superior results compared to other methods (Elith et al, 2006;Kumar et al, 2009;Phillips et al, 2006Phillips et al, , 2004Poulos et al, 2012). The prediction of the model indicates the areas within the study region that satisfy the requirements of the species' ecological niche.…”
Section: Vdc/distribution Modelling For Pterocarpus Angolensis -Appromentioning
confidence: 99%
“…This algorithm uses presence-only data of the variable of interest (i.e., burned polygons) to compare the values of the environmental predictors associated with these presence points with those of a background consisting of the means of all values of the environmental variables over the entire study area. MaxEnt has proven to be more conservative than other models in predicting probability of species occurrence (Kumar et al 2009), in part, because it adjusts for over fitting through a process of ''regularization,'' which prevents the algorithm from matching the observations too closely (Elith et al 2011).…”
Section: Modeling Spatial Probability Of Fire Occurrencementioning
confidence: 99%
“…Because conventional methods of remote sensing have limited applications for detecting tamarisk, our analyses were conducted using the Maxent software (v3.2.1; www.cs.princeton.edu/~schapire/maxent/), which uses presence points to predict the potential range and habitat distribution of a species [36,37]. In several recent studies, Maxent has been found to be especially useful for mapping invasive species [38,39] and ranked high when compared to other models for predicting tamarisk distributions [35]. We tested six satellite scenes and derived vegetation indices from different months of the growing season to detect tamarisk using single-scene and time-series analyses.…”
Section: Introductionmentioning
confidence: 99%